High prevalence of Mycobacterium tuberculosis mixed infection in the capital of moderate tuberculosis incidence country. (April 2016) - Hajimiri, Elahe Sadat; Masoomi, Morteza; Ebrahimzadeh, Nayereh; Fateh, Abolfazl; Hadizadeh Tasbiti, Alireza; Rahimi Jamnani, Fatemeh; Bahrmand, Ahmad Reza; Mirsaeidi, Mehdi; Vaziri, Farzam; Siadat, Seyed Davar
Abstract: Objective: Recent studies using molecular epidemiological techniques have demonstrated mixed infection with multiple strains of Mycobacterium tuberculosis especially in countries with high tuberculosis (TB) burden. We aimed to determine the prevalence of mixed infection among patients with TB in the capital of Iran as a country with moderate incidence rate. Methods: Samples were collected randomly from January 2011 to December 2013 in Tehran, capital of Iran. A total of 75  M. tuberculosis isolates were genotyped by 24 loci mycobacterial interspersed repetitive unit-variable number tandem repeat typing (MIRU-VNTR) for screening the mixed infection. Results: Twenty patients (20/75) were identified with mixed infection, and the estimated rate of mixed infection was 26.6%. Thirteen out of the 24 loci were able to detect the mixed infection in our study. Conclusions: Mixed infections occur at high prevalence among studied Iranian TB patients. Further research is inevitable to evaluate the association of mixed infection and disease progression and treatment. Highlights: The aim of the study was evaluating of mixed Mycobacterium tuberculosis infection in Iran. Mixed infection occurred at high prevalence among studied Iranian TB patients. In our study, thirteen out of the 24 loci were able to detect the mixed infection.